ANALISIS PELAKSANAAN PROGRAM RUMAH SAKIT TANPA DINDING (HOSPITAL WITHOUT WALLS) PADA FASE PRA HOSPITAL DI RSJD DR. AMINO GONDOHUTOMO - Annisa, Viona; Patria Jati, Sutopo; Budiyanti, Rani Tiyas (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2021)
Hospital without walls (HWW) Program was one of the leading programs of the Governor of Central Java for the 2018-2023 period, which was implemented by seven provincial hospital in Central Java, one of which is RSJD Dr. Amino Gondohutomo. Since the implementation of HWW program in 2018 until now, there has not been a comprehensive program evaluation by the HWW Implementing Coordinating Team for identifying from assessments that have been carried out. The evaluation was carried out only refers to the indicators of success in the guideline from quantity aspect, while in quality aspect has not been any further evaluation process with all the team members. So the purpose of this study was to evaluate the implementation of HWW Program at RSJD Dr. Amino Gondohutomo using the CIPP (Context, Input, Process, Product) evaluation theory by Daniel Stufflebeam. This research used qualitative methods with a descriptive approach through in-depth interview. There were 8 interviewees in this studied which consisting of 5 main informants and 3 triangulation informants. The variables studied were purpose, needs, target group, guidelines and SOP, action plans, human resource, funds, facilities and infrastructure, recording and reporting of planning and implementation program, and program achievement. The result showed that activity planning was still not well coordinated, SOP and governance document was not yet available, lack of competence for team members, recording and reporting of activities was not systematic and less structured. However there were supporting factors for the program, namely the formation of HWW Coordinating Team, an understanding of the objectives, budget and infrastructure were well fullfilled.Keywords : RSTD program, hospital without walls, evaluation